On-Farm Transport of Ornamental Fish - Tina C. Crosby; Jeffrey E. Hill; Carlos V. Martinez; Craig A. Watson; Roy P. Yanong (EDIS)
FA-119, a 6-page illustrated fact sheet by Tina C. Crosby, Jeffrey E. Hill, Carlos V. Martinez, Craig A. Watson, and Roy P.E. Yanong, describes how to reduce factors that contribute to stress in ornamental fish during transport from the grow-out pond to the holding facility. Includes recommended reading and references. Published by the UF Department of Fisheries and Aquatic Sciences, November 2006.